Towards the development of Sharī'ah compliant high quality liquid assets for Islamic financial institutions - Engku Ali, Engku Rabiah Adawiah; Oseni, Umar Aimhanosi; Ellias, Muhd Ramadhan Fitri; Haron, Muhamad Nasir (IIUM Press, International Islamic University Malaysia, 2017)
Islamic banks are required to be able to access and hold sufficientlevels of High Quality Liquid Assets (HQLA) as part of Basel IIIrequirements. Such HQLA are specifically meant to allow theIslamic banks to raise funds in money markets in the event ofliquidity shortage or in some cases for the funding of new profitableinvestments. Against this backdrop, this study examines existingefforts in developing Sharī’ah-compliant HQLA and the challengesIslamic financial institutions are facing in assessing such liquidinstruments. Beside the laudable efforts of a policy-drivensupranational institution in developing Sharī’ah-compliant HQLA,there has not been much effort in the global Islamic finance industryto develop more HQLAs. As a matter of fact, it is the overarchingdearth of such Sharī’ah compliant HQLA for liquidity managementthat led the Bank of England to commence work on the feasibility ofintroducing central bank liquidity facilities such as the proposedSharī’ah compliant fund based deposit in 2015 which is expected tobe ready for implementation by Spring 2018. This study also findsthat experts have considered the potential of gold as HQLA forbank’s liquidity management